Vibrational properties, crystal X-ray diffraction structure and quantum chemical calculations on a divalent sulfur substituted phthalimide: 1H-Isoindole-1,3(2H)-dione, 2-[(methoxycarbonyl)thio] - Torrico Vallejos, Sonia (2010)
Structural and conformational properties of 1H-Isoindole-1,3(2H)-dione,  2-[(methoxycarbonyl)thio] (Sphthalimido O-methyl thiocarbonate) are analyzed using a combined approach including X-ray diffraction, vibrational spectra and theoretical calculation methods. The vibrational properties have been studied by infrared and Raman spectroscopies along with quantum chemical calculations (B3LYP and B3PW91 functional in connection with the 6-311++G** and aug-cc-pVDZ basis sets). The crystal structure was determined by X-ray diffraction methods. The substance crystallizes in the monoclinic P21/c space group with a = 6.795(1), b = 5.109(1), c = 30.011(3) Å, b = 90.310(3)º and Z = 4 molecules per unit cell.The conformation adopted by the N-S-C=O group is syn (C=O double bond in synperiplanar orientation with respect to the N-S single bond). The experimental molecular structure is well reproduced by the MP2/aug-cc-pVDZ method.